Born or not: A moderated mediation model of the relationship between work-family conflict and female employees' wellbeing based on fertility intention during the COVID-19 pandemic - Zeng, Zhen; Ma, Jian; Ma, Yueru; Li, Dayuan; Sun, Yong (Frontiers in Public Health, 2023)
The previous academic research on work-family conflict mainly focused on the relevant elements in the work field.This study concludes that elements of the family domain have a significant impact on the relationship between work-family conflict and employee well-being. Female employees' perceptions of well-being largely depend on their willingness to have children when they take on family roles. during COVID-19, employees had more time to fulfill both work and family roles in the family sphere due to the epidemicblockade, the contribution of the female employee's significant other (husband) in family matters had a significant impact on Fertility intention. In the paired data of 412 working female employees and husbands of Chinese dual-earner families with different occupational backgrounds, hypothesis testing results support that female employees' work→family conflict is negatively related to female employees' fertility intentions, and female employees' fertility intentions are positively related to well-being; female employees' family→work conflict is negatively related to female employees' well-being; husband's flexible work stress is negatively related to husband's share of housework; husband's share of housework moderated the front, rear and overall mediating effects by the fertility intention.